Effects of Self-Concept on Narcissism: Mediational Role of Perceived Parenting - Farzand, Maryam; Cerkez, Yagmur; Baysen, Engin (Frontiers in Psychology, 2021)
An increase in narcissism has been reported by experts over the years. Narcissists bring a lot of negative consequences to themselves and to the people around them. This study investigates that perceived parenting leads to the development of inflated, unstable self-concept. The inflated self-concept lays the framework for the development of narcissistic traits among individuals; perceived parenting affects this relationship. A sample of 628 adults was taken from North Cyprus through purposive sampling. Scales for perceived parenting, self-concept, and narcissism were administered. Results showed that the statistically significant variance in the self-concept is explained by perceived parenting. Both mothers and fathers contributed significantly to the development of inflated self-concept. Moreover, multiple linear regression results showed a higher significant variance in narcissistic traits due to self-concept compared with perceived parenting. Mediational tests also showed that high levels of narcissistic traits were indirectly related to self-concept through perceived parenting. The study findings have challenged the notion of only mothers being responsible for narcissistic traits among their children. The study results also suggest that targeting self-concept in individuals with narcissistic traits may be a good directive for therapeutic interventions.